Ruthenium water oxidation catalysts containing the non-planar tetradentate ligand, biisoquinoline dicarboxylic acid (biqaH2). Issue 48 (23rd November 2016) - Scherrer, Dominik; Schilling, Mauro; Luber, Sandra; Fox, Thomas; Spingler, Bernhard; Alberto, Roger; Richmond, Craig J.
Abstract : Influences on water oxidation catalysis caused by elaboration of the equatorial ligand framework from bipyridine to biisoquinoline. Abstract : Two ruthenium complexes containing the tetradentate ligand [1, 1′-biisoquinoline]-3, 3′-dicarboxylic acid, and 4-picoline or 6-bromoisoquinoline as axial ligands have been prepared. The complexes have been fully characterised and initial studies on their potential to function as molecular water oxidation catalysts have been performed. Both complexes catalyse the oxidation of water in acidic media with Ce IV as a stoichiometric chemical oxidant, although turnover numbers and turnover frequencies are modest when compared with the closely related Ru-bda and Ru-pda analogues. Barriers for the water nucleophilic attack and intermolecular coupling pathways were obtained from density functional theory calculations and the crucial influence of the ligand framework in determining the most favourable reaction pathway was elucidated from a combined analysis of the theoretical and experimental results.